Implementasi Prinsip Komunikasi Islam Pengasuh dalam Membina Akhlak Remaja di Panti Asuhan Baitul Umma Wal Amal Marelan - Siregar, Novi Miani; Simaora, Irma Yusriani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to determine the implementation of Islamic communication principles for caregivers in developing morals for teenagers at the Baitul Umma Wal Amal Marelan Orphanage. This research uses a descriptive qualitative method with a field research approach. This research data comes from observations, interviews and documentation studies. This research data was analyzed through a process of data reduction, data presentation, and drawing conclusions. The validity of this research data was determined through triangulation techniques. The results of this research show that the principles of Islamic communication, such as qoulan sadida (speak honestly and to the point), qoulan ma'rufa (speak well and politely), qoulan layina (speak gently), and qoulan karima (speak fully). respectful and noble), implemented consistently in guiding teenagers. Through daily activities that harmonize religious, educational and recreational obligations, this institution not only creates an educational environment but also builds a strong foundation in the formation of positive morals and character in its residents. Thus, these principles not only increase the effectiveness of communication, but also provide a solid moral foundation in daily interactions, reflecting deep attention to the personal and social development of adolescents in these orphanages.